2004
DOI: 10.1002/hrm.20027
|View full text |Cite
|
Sign up to set email alerts
|

Performance management and assessment: Methods for improved rater accuracy and employee goal setting

Abstract: IntroductionPerformance management systems in organizations should rest on principles of good management supported by extensive research in organizational psychology and human resource management. Basic methods of performance management encompass dimensions of performance, goals for performance and career development, training and development programs, supervisory performance appraisal, multisource performance ratings, feedback, coaching, and rewards. Unfortunately, human resource practitioners and managers ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 33 publications
0
42
0
3
Order By: Relevance
“…; Hedge & Teachout, 2000;Murphy & Cleveland, 1995), accuracy indices are still commonly used to investigate performance ratings (London, Mone, & Scott, 2004). For example, in the last 3 years, Cronbach's accuracy indices were used as indicators of rating quality in several empirical studies (e.g., Bernardin, Tyler, & Villanova, 2009;Gorman & Rentsch, 2008;Melchers, Kleinmann, & Printz, 2010;Melchers, Lienhardt, von Aarburg, & Kleinmann, 2011;Uggerslev & Sulsky, 2008).…”
Section: Discussionmentioning
confidence: 98%
“…; Hedge & Teachout, 2000;Murphy & Cleveland, 1995), accuracy indices are still commonly used to investigate performance ratings (London, Mone, & Scott, 2004). For example, in the last 3 years, Cronbach's accuracy indices were used as indicators of rating quality in several empirical studies (e.g., Bernardin, Tyler, & Villanova, 2009;Gorman & Rentsch, 2008;Melchers, Kleinmann, & Printz, 2010;Melchers, Lienhardt, von Aarburg, & Kleinmann, 2011;Uggerslev & Sulsky, 2008).…”
Section: Discussionmentioning
confidence: 98%
“…In particular, frame-of-reference (FOR) training is one possible approach for improving rater reliability and accuracy (London et al 2004;Schleicher et al 2002). FOR training changes the impression formation process of raters to more trait-based (as opposed to behavioral-based) representations of the ratee (Schleicher et al 2002).…”
Section: Implications and Future Research Directionsmentioning
confidence: 99%
“…The presumption is that people who participate in setting goals are likely to be more motivated to achieve them than those who are given goals created by others (London et al 2004). With regard to group efficacy, it is asserted that team-level goal setting can potentially increase cohesiveness, establishment of norms and routines, and increased efficiency of information processing.…”
Section: Pe Theorymentioning
confidence: 97%
“…A number of studies in goal-setting theory are the effect of participative goal setting (PGS) on employee performance and attitude. The presumption is that people who participate in setting goals are likely to be more motivated to achieve them than those who are given goals created by others (London, Mone and Scott 2004). However, reviews addressing the use of participation in goal setting (Mitchell 1979;Locke and Latham 1984;Erez and Arad 1986;Mento, Steel and Karren 1987) have all concluded that the relationship between participation and performance is inconsistent and unclear; participative vs. assigned goal setting is inconclusive and must await further research.…”
Section: Introductionmentioning
confidence: 96%